The stakeholders ecosystem of waqf institutions in Malaysia - Hamdan, Norman; Osman@Hussin, Ahmad Zamri; Ab Rashid, Hafiz-Majdi (Universiti Malaya, 2019)
Improved accounting and reporting practice for waqf institution in Malaysia has become an indispensable necessity. The identification of waqf stakeholders may help the institution to achieve this objective as the interest of these accounting users are to be properly addressed in the financial reports. This paper investigates the stakeholders of waqf and their relationship with waqf institution. Semi-structured interviews have been conducted involving 27 waqf managers and accountants from various organizations in waqf institution. Based on the thematic analysis, 18 groups of waqf stakeholders and three categories of stakeholder influential relationship have been identified. The results of this study provided a basis for waqf institution to further